Antibody persistence and Haemophilus influenzae type b carriage after infant immunisation with PRP-T. Issue 6 (1st December 1997) - Heath, P T; Bowen-Morris, J; Griffiths, D; Griffiths, H; Crook, D W M; Moxon, E R
Abstract : OB JECTIVES: To assess the persistence of serum Haemophilus influenzae type b antibodies and the prevalence of H influenzae type b carriage in a group of preschool age children previously vaccinated in infancy. DESIGN: Names were randomly selected from immunisation records. Families were visited on five occasions over a period of 12 months and throat swabs were taken from all family members present, with blood obtained from children at the first and last visits. RESULTS: One hundred and fifty three children at a median age of 3.6 years had a geometric mean titre (GMT) of 1.06 μg/ml (95% CI 0.80 to 1.38). Eight per cent had an undetectable antibody concentration, received a booster dose of plain PRP vaccine, and responded with concentrations > 2 μg/ml. GMT at 4.5 years of age was 0.89 μg/ml (0.69 to 1.16). Twelve children who had been exposed to H influenzae had a GMT of 4.7 v 0.8 μg/ml for those without exposure. CONCLUSIONS: Accelerated immunisation against H influenzae without a second year booster results in persistence of satisfactory serum concentrations of antibody to 4.5 years of age. In those with undetectable antibody, immunological memory may still be present.